2010
DOI: 10.1186/1752-1947-4-93
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the renal vein during pyelography after nephrostomy: a case report

Abstract: IntroductionWe present a case of pyelovenous backflow after nephrostomy. To the best of our knowledge, this is the first documented case of renal vein visualization after a nephrostomic placement.Case presentationA 55-year-old Caucasian man presented with symptoms of pyelonephritis with an obstructing ureteral stone. A nephrostomy was performed. During an injection of contrast agent in his left caliceal system, his left renal vein was visualized. A repeat pyelography with an injection contrast material at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…They are considered to be compensatory mechanisms that allow the kidney to continue urine excretion . Among them, PVB is hypothesized to result from the veno‐caliceal fistula or the synchronous rupture of a vein within the renal calyceal fornix …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered to be compensatory mechanisms that allow the kidney to continue urine excretion . Among them, PVB is hypothesized to result from the veno‐caliceal fistula or the synchronous rupture of a vein within the renal calyceal fornix …”
Section: Discussionmentioning
confidence: 99%
“…5 Among them, PVB is hypothesized to result from the veno-caliceal fistula or the synchronous rupture of a vein within the renal calyceal fornix. 6,7 Contrast-enhanced CT is considered an alternative tool for identifying PVB in cases where RP is not applicable. Nemeth et al reported the first case where excretory phase CT revealed PVB flowing into the IVC in a patient with an abdominopelvic abscess after a cesarean section delivery.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few cases and experimental animal studies presented in the literature that were conducted with the help of conventional radiographic techniques [ 1 , 3 , 5 , 6 ]. However, this computed tomography case revealed increased density and streaks, which started at the renal sinus and continued caudally with a lace-like pattern surrounding the proximal ureter within the retroperitoneal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Abdallah Geara presented a case of visualization of the renal vein during pyelography after nephrostomy, and examination by microscopy showed the presence of tears in the fornix of the pelvic cavity that extend into the kidney parenchyma [ 7 ]. However, significant venous injuries during percutaneous renal surgery probably are under diagnosed [ 8 ].…”
Section: Discussionmentioning
confidence: 99%